"Castigat Ridendo Mores": o humor costumbristas nas páginas do periódico A Encrenca (1914-1915), de Caxias do Sul - Ferretti, Liliana Cainelli Cambruzzi (My University, 2019)
The present dissertation investigates, through the methodology of content analysis, how humor humor is present in A Encrenca, especially in the column Janellisces, and in which categories of humor the newspaper operates, aiming to contribute to studies on humor and regional press of the Serra Gaúcha. With a multidisciplinary theoretical contribution, covering the areas of Social Communication, History, Sociology, Letters and Literature, we sought to contextualize the Region of Italian Colonization in Rio Grande do Sul from the beginning of immigration to 1914, year of publication of the newspaper, including the emergence and development of the press local. Also relevant was the survey of humor theories, especially the categories listed by Vladimir Propp, as well as data on the beginning of the humorous press in Brazil, and later on in Rio Grande do Sul and Serra Gaúcha. Based on the bibliographic review, it was possible to perform the analysis of the representations present in the corpus. At the end of this work, it is evident how the newspaper's mockery pen made use of the humorous resources in its textual production with a focus on costumbrismo, seeking through laughing to put in discussion habits of the society.
A presente dissertação investiga, por meio da metodologia de análise de conteúdo, de que forma o humor costumbrista está presente no A Encrenca, em especial na coluna Janellisces, e em que categorias de humor o jornal opera, com vistas a contribuir para os estudos sobre o humor e imprensa regional da Serra Gaúcha. Com aporte teórico multidisciplinar, contemplando as áreas da Comunicação Social, História, Sociologia, Letras e Literatura, buscou-se contextualizar a Região de Colonização Italiana no Rio Grande do Sul dos primórdios da imigração a 1914, ano de lançamento do jornal, incluindo o surgimento e desenvolvimento da imprensa local. Também fez-se relevante o levantamento das teorias do humor, em especial, as categorias elencadas por Vladimir Propp, além de dados sobre o início da imprensa humorística no Brasil, e posteriormente no Rio Grande do Sul e na Serra Gaúcha. Com base na revisão bibliográfica, foi possível realizar a análise das representações presentes no corpus. Ao final deste trabalho, evidencia-se como a pena pilhérica do jornal fazia uso dos recursos humorísticos em sua produção textual com foco no costumbrismo, buscando por meio do riso colocar em discussão hábitos da sociedade.
Keywords: Imprensa; Humorismo; Jornalismo - Caxias do Sul (RS); Press; Wit and humor; Journalism - Caxias do Sul (Brazil)